Growing Acts of Indiscipline in Ghanaian Schools: Perception of Students and Teachers at Abuakwa South Municipality (International Journal of Scientific Research and Management (IJSRM), 2018)
Indiscipline in schools has attracted the attention of many people and has eventually become the focus of discussions on many platforms. The purpose of the study was to find out the perceptions of teachers and students at the Abuakwa South Municipality of Ghana on student indiscipline behaviours. The study employed the descriptive survey and the approach was concurrent mixed method, involving both quantitative and qualitative paradigms. Purposive and simple random sampling methods were used to obtain a sample size of five hundred and thirty (530) respondents. The main instruments used for the study were questionnaire and a semi-structured interview guide. Data was analysed using inferential statistics and content analysis. Findings from the study revealed that; there was no perceptual difference between students and teachers views on acts that constitute disciplinary behaviours. Additional, there were differences in the students’ and teachers’ perceptions of the influences of peer pressure on students’ disciplinary behaviours. It was recommended among others that peer counselling sessions should be organized periodically among students for them to be aware of acceptable behaviours in the school system and how they can maintain desirable behaviours.